College as a marriage market - Lars J. Kirkebøen; Edwin Leuven; Magne Mogstad (Statistics Norway, Research Department, 2021)
Recent descriptive work suggests the type of college education (field or institution) is an important but neglected pathway through which individuals sort into homogeneous marriages. These descriptive studies raise the question of why college graduates are so likely to marry someone within their own institution or field of study. One possible explanation is that individuals match on traits correlated with the choice of education, such as innate ability, tastes or family environment. Another possible explanation is that the choice of college education causally impacts whether and whom one marries, either because of search frictions or preferences for spousal education. The goal of this paper is to sort out these explanations and, by doing so, examine the role of colleges as marriage markets. Using data from Norway to address key identification and measurement challenges, we find that colleges are local marriage markets, mattering greatly for whom one marries, not because of the pre-determined traits of the admitted students but as a direct result of attending a particular institution at a given time.
Keywords: D13; I23; I24; J12; 330; assortative mating; college; educational homogamy; field of study; marriage market; search frictions; Hochschule; Akademiker; Partnerwahl; Ehe; Norwegen